Overcoming Market Failures in Pandemic Drug Discovery Through Open Science: A Canadian Solution - Gold, E. Richard; Edwards, Aled M. (Frontiers in Drug Discovery, 2022)
Among the lessons learned from the COVID-19 pandemic is the need to develop antiviral drugs poised to treat the next pandemic. Unfortunately, traditional drug development economic models, centered principally on patents, are ineffective to induce private sector investment due to unpredictable timing and cause of the next pandemic. As a result, illustrated by the COVID-19 pandemic, it is the public and philanthropic sectors sectors that overwhelmingly fund the development of innovative vaccines and therapies. To meet the need for proactive antiviral medicines in advance of the next pandemic, new models of drug development are needed. Open science partnerships (OSPs) show promise in this regard. Rather than rely principally on patents and private investment, OSPs combine a variety of academic, philanthropic, governmental, and private sector incentives to share knowledge and develop and test antiviral drugs. Private sector investments are, within an OSP, not only leveraged against investments by other actors, but predicated on gaining regulatory data exclusivity, a known and secure form of commercial advantage. Building on domestic expertise in OSPs, Canadian leaders created the Viral Interruption Medicines Initiative, a not-for-profit OSP, to develop pandemic ready-antivirals and address other areas of market failure.